Clinical implantation of 92 VACStents in the upper gastrointestinal tract of 50 patients—applicability and safety analysis of an innovative endoscopic concept - Lange, J.; Knievel, J.; Wichmann, D.; Kähler, G.; Wiedbrauck, F.; Hellmich, T.; Kandler, M.; Bernhardt, J.; Scholz, D.; Beyna, T.; Hausmann, J.; Wedi, E.; et al. (Frontiers in Surgery, 2023)
Introduction Endoscopic vacuum therapy (EVT) has emerged as a promising treatment option for upper gastrointestinal wall defects, offering benefits such as evacuation of secretions and removal of wound debris by suction, and reduction and healing of wound cavities to improve clinical outcomes. In contrast, covered stents have a high rate of migration and lack functional drainage, while endoluminal EVT devices obstruct the GI tract. The VACStent is a novel device that combines the benefits of EVT and stent placement. Its design features a fully covered Nitinol-stent within a polyurethane sponge cylinder, enabling EVT while maintaining stent patency. Methods This study analyzes the pooled data from three different prospective study cohorts to assess the safe practicality of VACStent placement, complete leak coverage, and effective suction-treatment of esophageal leaks. By pooling the data, the study aims to provide a broader base for analysis. Results In total, trans-nasal derivation of the catheter, suction and drainage of secretion via vacuum pump were performed without any adversity. In the pooled study cohort of 92 VACStent applications, the mean stent indwelling time was 5.2 days (range 2–8 days) without any dislocation of the device. Removal of the VACStent was done without complication, in one case the sponge was lost but subsequently fully preserved. Minor local erosions and bleeding and one subsequent hemostasis were recorded unfrequently during withdrawal of the device (5.4%, 5/92) but no perforation or pressure ulcer. Despite a high heterogeneity regarding primary disease and pretreatments a cure rate of 76% (38/50 patients) could be achieved. Discussion In summary, insertion and release procedure was regarded as easy and simple with a low potential of dislocation. The VACStent was well tolerated by the patient while keeping the drainage function of the sponge achieving directly a wound closure by continuous suction and improving the healing process. The implantation of the VACStent provides a promising new procedure for improved clinical treatment in various indications of the upper gastrointestinal wall, which should be validated in larger clinical studies. Clinical Trial Registration: Identifier [DRKS00016048 and NCT04884334].